(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this paper, the features of heat and mass transfer processes inside the dried product are studied by mathematical modeling. The previously obtained experimental results on the study of the drying rate of products have been confirmed by calculation. Calculations show that the drying rate – the movement of moisture in the volume of products depends on its thickness, with its increase, the drying rate of products decreases, which has been confirmed by experiments. As the comparison of the obtained data shows, the discrepancy between the calculated and experimental results is no more than 5%, which shows the high reliability of the obtained mathematical model of heat and mass transfer processes for its use in calculations for the study of similar processes.